Incentives to conserve or convert? Can conservation compete with coal in Kutai National Park, Indonesia? - Limberg, G.; Moeliono, M.; Indriatmoko, Y.; Iwan, R.; Utomo, N.A.; Purwanto, E.; Mulyana, A. (2009)
Discussions on climate change and potential mechanisms to support conservation efforts have fixed the attention on incentives to conserve and protect forests. However, incentives alone will not do the job for forest conservation; what might? We use the case of Kutai National Park to examine the potential for incentives to boost conservation and the urgent need to simultaneously apply disincentives against conversion of the park. Kutai National Park is an extreme case: conservation values have to compete with the value of vast deposits of high-grade coal. The park management unit has tried to calculate the conservation benefits derived from the park ecosystem, but these values are miniscule compared to the alternatives of mining and logging. Incentives for encroachment and the conversion of the park are the easily accessible timber and enormous known coal deposits. These resources provide immediate tangible benefits for the settlers in the park and the local government to exploit the park, and affect local possibilities for conserving it. If we are to be serious about conserving important ecosystems, incentives alone are insufficient. Action is needed to ensure that all stakeholders support the national government’s commitment to preserve representative examples of biodiversity and ecosystems; each stakeholder will have to make some sacrifices.